Physical Exercise and Yoga: As an Alternative Approach Towards COVID-19 Management - Kumar, Saurabh; Sudha, Sakshi; Chopra, Madhu; Khan, Famida; Sharma, Kanupriya (Current Traditional Medicine, 2021)
Background: Novel Coronavirus (COVID-19), a highly contagious ssRNA +Ve sense virus that emerged in late 2019, has created a global panic. With no effective therapy available, the virus has significantly affected the world population causing millions of death. Therefore, it is the utmost need to look towards all the possible strategies to benefit the community. Objectives: In view of the current global pandemic, we tried to discuss the potential benefits of two cost-effective alternative approaches, i.e., physical exercise and yoga. Methods: The editorial is based on a literature search available on PubMed, Google Scholar, and WHO portal. Search terminologies include “yoga,” “physical exercise,” “COVID-19,” “viral infections,” and a combination of these words. Results: A literature search defines yoga and physical exercise efficacy in different viral diseases, including HIV, influenza, and HSV. It ameliorates the quality of life (QoL) by improving both the physical and mental well-being of an individual. This is mainly done by promoting the better functioning of the immune system (increases CD4+ and CD8+ cells and reduces pro-inflammatory response). Conclusions: Regular involvement of these activities in day-to-day life may limit latent virus reactivations and reduce infection chances.
Keywords: viral infection